Social Media as an Early Warning System for Drug Prevention: Case Study of Surabaya's Digital Surveillance Program - Ismail, Ismail; Felecia, Felecia; Azizah, Anisa Kurniatul; Rahmawati, Diana (The Eastasouth Journal of Information System and Computer Science, 2025)
Social media has emerged as a powerful tool in public health initiatives, including drug prevention efforts. This study examines the role of social media as an early warning system in the Digital Surveillance Program in Surabaya. Using a quantitative approach with a sample of 100 respondents, data was collected through a Likert-scale questionnaire (1–5) and analyzed with Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results reveal that public awareness significantly influences social media engagement and program effectiveness, while social media engagement plays a critical role in enhancing program outcomes. The structural model demonstrates moderate predictive power (R² = 0.53 for program effectiveness), highlighting the importance of integrating public awareness campaigns and social media engagement strategies to optimize drug prevention initiatives. The findings provide actionable insights for policymakers and stakeholders, emphasizing the need for community-centered content creation and data-driven social media strategies to combat drug misuse.